2008
DOI: 10.1002/mawe.200800274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical property analysis of Nitinol defective stent under uniaxial loading/unloading

Abstract: The vascular stents are important medical devices introduced into a vessel to protect the lumen from unfriendly stenosis. However, Nitinol stent is easy to fail in practice. The present paper focuses on the influence of defects on its mechanical behavior by finite element analysis. The essential stent cell is used with two different type of defects, which includes the face bulge defect resulted from laser burrs or TiC inclusion arises and C-contained particle voids. Auricchio's super-elastic consititutive equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This is in good agreement with previous results on laser-cut stents, where it was observed that TiC particles can act as microcrack initiation sites [11]. It was also found that a stent is more likely to fail if these particles are situated close to geometrical knots and notches [18]. Figure 13b suggests that such cracks can link up during cyclic mechanical loading and form bigger cracks.…”
Section: Surface Inspection Of Braided Stentssupporting
confidence: 86%
“…This is in good agreement with previous results on laser-cut stents, where it was observed that TiC particles can act as microcrack initiation sites [11]. It was also found that a stent is more likely to fail if these particles are situated close to geometrical knots and notches [18]. Figure 13b suggests that such cracks can link up during cyclic mechanical loading and form bigger cracks.…”
Section: Surface Inspection Of Braided Stentssupporting
confidence: 86%
“…Fig. 1(f) shows the geometry of a common stent (Zhi et al, 2008). The mesh elements are filleted at the blending points, where their tangent changes continuously.…”
Section: Lattice Cells With Smooth Shape Elementsmentioning
confidence: 99%
“…For example, Fig. 1(f) shows the structural geometry of a recent stent consisting of a 2D lattice of closed cells (Zhi et al, 2008). At the blending points between the arcs and the linear segments of each cell, the curvature is not smooth.…”
Section: Introductionmentioning
confidence: 98%